Event study on the impact of the COVID-19 outbreak on the Malaysia stock market returns / Farah Hayati Mustapa - Mustapa, Farah Hayati (UiTM Cawangan Negeri Sembilan, 2022)
This study investigates the impact of the COVID-19 outbreak on the Malaysia stock market returns. We perform an 'event study' to investigate the effect of the announcement of the coronavirus as a global pandemic by the World Health Organization on 11th March 2020, on the KLCI stock returns. The historical stock prices, before, on and after the announcement date, from each 30 components of KLCI were analysed. The results show that there is a significant difference in abnormal returns among days before and after the announcement date. Moreover, the Malaysia stock market is negatively impacted by the pandemic announcement. Therefore, we can conclude that the Malaysia stock market is inefficient at the semi-strong level and that the stock prices do not reflect the change in the stock market instantly.